2004
DOI: 10.1007/s00429-004-0390-5
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelial lamellar bodies in norm and experimental conditions. Transmission and scanning electron microscopic observations on the peritoneum, pleura and pericardium

Abstract: The ultrastructural characteristics of the mesothelial intracellular and extracellular lamellar bodies (LB) in norm, and especially in pathological conditions are still unknown. After routine fixation procedure, material from organs in the three serous cavities of Wistar rats, as control group were compared with animals following experimental hemothorax (EH) and experimental peritonitis (EP), using transmission and scanning electron microscopy (TEM, SEM). Different membrane-bound profiles, short strip-like str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…It has been previously reported that healthy mesothelial cells can prevent tumor cell invasion and metastasis by providing an intact barrier. Interestingly, tumor cells are also known to secrete various factors to induce damage or apoptosis in mesothelial cells and the disrupted mesothelial cells will then promote tumor cells invasion (17)(18)(19). We hypothesize that the damaged peritoneum may provide such a microenvironment for scirrhoid gastric cancer cell metastasis.…”
Section: Discussionmentioning
confidence: 95%
“…It has been previously reported that healthy mesothelial cells can prevent tumor cell invasion and metastasis by providing an intact barrier. Interestingly, tumor cells are also known to secrete various factors to induce damage or apoptosis in mesothelial cells and the disrupted mesothelial cells will then promote tumor cells invasion (17)(18)(19). We hypothesize that the damaged peritoneum may provide such a microenvironment for scirrhoid gastric cancer cell metastasis.…”
Section: Discussionmentioning
confidence: 95%
“…There are numerous vesicles, vacuoles and multivesicular bodies, as well as the signs of the robust vesicle formation at the cell membranes in the form of either coated or uncoated vesicles being in the process of internalization from or budding of the cell membranes ( Figure 1). In addition, the cytoplasm of cuboidal cells contains numerous vesicles/vacuoles filled entirely or partially with an electron-dense material, sometimes displaying a multilamellar appearance, often described as dense bodies [8] (Figure 1). These structures are believed to contain surfactant-like substances, similar to those produced by type II pneumocytes [8].…”
Section: The Ultrastructure Of the Pericardiummentioning
confidence: 99%
“…In addition, the cytoplasm of cuboidal cells contains numerous vesicles/vacuoles filled entirely or partially with an electron-dense material, sometimes displaying a multilamellar appearance, often described as dense bodies [8] (Figure 1). These structures are believed to contain surfactant-like substances, similar to those produced by type II pneumocytes [8]. The apical surface of cuboidal cells is covered by abundant microvilli, having the length of up to 3 μm [3][4][5][6][7]; some of the microvilli bifurcate near their ends.…”
Section: The Ultrastructure Of the Pericardiummentioning
confidence: 99%
“…Their presence has been later suggested also on pleura, peritoneal and pericardial mesothelium [12,[30][31][32][33]. Actually, by transmission electron microscopy, Wang [12] and Ohtsuka [32] found that colloidal iron stain of mesothelial glycocalyx is removed by neuraminidase treatment, which cleaves sialic acid from sialomucin.…”
Section: Sialomucin Lubricant Effectsmentioning
confidence: 99%
“…Moreover, in samples of human and rat peritoneum, Dobbie and Anderson [49], and Michailova [33] provided electron microscopy evidence of several lamellar bodies among the microvilli, and of some superficial lamellar membranes. Unfortunately, no information is available on the spatial and functional relationships between these phospholipids layers and the mucopolysaccharides coat of the mesothelial surface glycocalyx under physiological conditions.…”
Section: Phospolipids Lubricant Effectsmentioning
confidence: 99%